Laughter, Humor, and Cancer: Delicate Moments and Poignant Interactional Circumstances. Issue 7 (3rd July 2017) - Beach, Wayne A.; Prickett, Erin
ABSTRACT: Conversation analysis is employed to examine transcribed excerpts drawn from a subsample of 75 naturally occurring and video recorded interviews between cancer patients and 30 doctors. Close examination is provided of how cancer patients initiate, and doctors respond, to laughter and humor during oncology interviews. Interactions demonstrate that communication about the disease "cancer" shares qualities similar to other medical areas (e.g., primary care): the tendency for patients to initiate laughter or humor to address troubling and challenging circumstances; and that during moments when patients address personal matters, doctors are not invited and do not reciprocate with shared laughter and humor. Prominent in talk about cancer are various precarious circumstances, awkward and delicate moments mirroring the lived experiences of cancer patients (e.g., when patients attempt to minimize fears, justify that they are well when threatened with sickness, claim normality in the midst of chronic conditions, and take stances that weight loss and gain are not problematic). These examples provide a compelling case that routine cancer care involves many poignant situations managed through laughter and humor. Implications are raised for how quality care might be improved through grounded understandings of laughter, humor, and cancer.